2021
DOI: 10.1021/acschemneuro.1c00666
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between SARS-CoV-2 N-Protein and α-Synuclein Accelerate Amyloid Formation

Abstract: First cases that point at a correlation between SARS-CoV-2 infections and the development of Parkinson’s disease (PD) have been reported. Currently, it is unclear if there is also a direct causal link between these diseases. To obtain first insights into a possible molecular relation between viral infections and the aggregation of α-synuclein protein into amyloid fibrils characteristic for PD, we investigated the effect of the presence of SARS-CoV-2 proteins on α-synuclein aggregation. We show, in test tube ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
119
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(121 citation statements)
references
References 53 publications
1
119
1
Order By: Relevance
“…Recently, in vitro study reported that proteins from SARS-CoV-2, which causes COVID-19, interact with α-syn, speeding up the formation of amyloid plaques ( Semerdzhiev et al, 2021 ) open an interesting research field associating virus infections with PD or other neurodegenerative diseases development.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in vitro study reported that proteins from SARS-CoV-2, which causes COVID-19, interact with α-syn, speeding up the formation of amyloid plaques ( Semerdzhiev et al, 2021 ) open an interesting research field associating virus infections with PD or other neurodegenerative diseases development.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that SARS-CoV-2 neuroinfection leads to elevated alpha-synuclein levels [ 6 , 24 ]. Alpha-synuclein is a presynaptic protein expressed among others in the substantia nigra and thalamus and is one of the major constituents of Lewy bodies.…”
Section: The Neurotropic Potential Of Sars-cov-2 and Its Possible Rol...mentioning
confidence: 99%
“…Experimental studies showed that a persistently elevated level of alpha-synuclein promotes the formation of aggregates that are characteristic for neurodegenerative diseases including PD [ 29 , 31 ]. Semerdzhiev et al identified a SARS-CoV-2 protein that promotes aggregation of the alpha-synuclein in a test tube [ 6 ]. The acceleration of the onset of alpha-synuclein aggregation was observed in the presence of the SARS-CoV-2 nucleocapsid protein (N-protein).…”
Section: The Neurotropic Potential Of Sars-cov-2 and Its Possible Rol...mentioning
confidence: 99%
See 2 more Smart Citations